The Effect of Liquid Organic Fertilizer of Stale Rice and Sediment of Catfish Ponds on the Growth of Chili Plants (Capsicum annuum L.) - Winandari, Ovi Prasetya; Anisya, Shinta; Marantika, Sapta; Widiani, Nurhaida; Novitasari, Aulia (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Samudra, 2025)
riculture in Indonesia produces various types of plants such as staple foods such as rice, corn and vegetables. Vegetables that contain a lot of nutrients include chili plants. The productivity of chili plants in Indonesia is still relatively low, one of the factors is the low soil fertility due to the use of inorganic fertilizers. Therefore, alternative organic fertilizers are made from restaurant/household waste, one of which is rice waste and sediment water from catfish ponds that can be recycled. This study aims to evaluate the impact of using liquid organic fertilizer (LOF) derived from fermented rice and catfish pond sediment on the growth of curly red chili plants (Capsicum annum L.). The research utilized a completely randomized design (CRD) with a factorial model comprising two factors. The first factor was LOF made from fermented rice (Factor M), and the second was LOF from catfish pond sediment (Factor N). Each factor was tested at three treatment levels, resulting in nine treatment combinations. Each combination was replicated three times, along with three replications for a negative control, totaling 30 experimental units. Data analysis was conducted using ANOVA, followed by post-hoc testing with the Least Significant Difference (LSD) method at a 5% significance level. The findings indicated that the optimal results were achieved with the N3M3 treatment combination, which involved a dose of 300 ml of fermented rice LOF and 300 ml of catfish pond sediment LOF per liter of water. This combination yielded the best performance in terms of plant height, leaf count, fresh weight, and dry weight.